Intensities of exercise during match-play in FA Premier League referees and players - Weston, M.; Drust, B.; Gregson, W. (Journal of Sports Sciences, 2011)
The aim of the present study was to examine the relationship between intensities of exercise during match-play of elite-standard soccer referees with those of the players from the same match. Match analysis data were collected (Prozone® Leeds, UK) for 18 elite-standard soccer referees (age 26-49 years) on FA Premier League matches during the 2008/09 English FA Premier League season (236 observations). Running categories for referees and players were as follows: total distance covered (m); high-speed running distance (speed >19.8 km/h); and sprinting distance (speed >25.2 km/h). Analysis of the distance-time regression coefficients revealed no differences between the referees' and players' within-match rates of change for total distance covered (-0.594 ± 0.394 vs. -0.713 ± 0.269 m · min-1; P = 0.104), high-speed running (-0.039 ± 0.077 vs. -0.059 ± 0.030 m/min; P = 0.199), and sprinting (-0.003 ± 0.039 vs. -0.021 ± 0.017 m/min; P = 0.114). In addition, there were no differences between across-season rates of change for total distance (-26.756 ± 40.434 vs. -20.031 ± 25.502 m per match day; P = 0.439) and sprinting (-9.662 ± 7.564 vs. -8.589 ± 4.351 m per match day; P = 0.542). These results show that elite-standard soccer referees' intensities of exercise during match-play are interrelated with those of the players and thus demonstrate that referees are able to keep pace with the players during FA Premier League matches.